A Study on the Content of Eco Enzyme from Pineapple Peel (Ananas comosus L.) and Watermelon (Citrullus lanatus) - Widya Lestari (UIN Sulthan Thaha Saifuddin Jambi, 2023)
Fruits widely consumed and cultivated by the Indonesian community include pineapple (Ananas comosus L.) and watermelon (Citrullus lanatus). The utilization of both fruits generates waste in the form of fruit peels. Pineapple and watermelon peels can be utilized as raw materials for eco enzyme production with the addition of water and molasses. Several functions of eco enzyme include serving as a floor cleaner, vegetable and fruit cleaner, insect repellent, and plant fertilizer. Additionally, it functions as a disinfectant due to its alcohol and acetic acid content. The objective of this research is to analyze the eco enzyme product using parameters such as pH, TDS, alcohol content, color, aroma, and final volume. The raw materials for eco enzyme are divided into three groups: 1) pineapple peels; 2) watermelon peels; 3) a mixture of pineapple and watermelon peels. The method involves mixing water, fruit peels, and molasses in a ratio of 10:3:1 and incubating for 30, 60, and 90 days. Based on the research results, the pH values range from 3.4 to 3.6. The TDS values increase for all raw materials except in the group of pineapple peel raw materials. The alcohol content in the eco enzyme product remains unchanged after incubation. The eco enzyme produced exhibits a cloudy brown color on the 90th day of incubation. The aroma produced is characteristic of fermentation, consistent with the concentration of raw materials used. The highest final volume of the eco enzyme product is observed on the 90th day of incubation.